KEKUATAN HUKUM KWITANSI SEBAGAI BUKTI JUAL BELI BAWAH TANGAN ATAS SEBIDANG TANAH DALAM PUTUSAN NOMOR 135/PDT.G/2021/PN.PBR - Rifka Hidayani; Mohammad Fajri Mekka Putra (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
This study aims to analyze the considerations of the District Court judge who granted the lawsuit regarding the validity and value of a receipt as evidence of an underhand sale and purchase of a piece of land and the legal consequences of granting a lawsuit regarding the legality and value of a receipt as evidence of an underhand sale and purchase of a piece of land in Decision Number: 135 /PDT.G/2021/PN.Pbr. The research approach used is normative juridical law research or library research, with descriptive research type. The data analysis method used is qualitative. The results of this study indicate that the consideration of the District Court judge who granted the lawsuit regarding the validity and value of the receipt as evidence of an underhand sale and purchase of a piece of land is that the plaintiff as the buyer has good intentions in the buying and selling process, the basis of the lawsuit is not contrary to the laws and regulations and does not against the law.